MODEL NUMBERED HEADS TOGETHER TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV - Husni Wakhyudin; Risty Juliyanti (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
This research was purpose to find out the effect of Numbered Heads Together model toward problem solving ability of thematic integrative learning of IV SD Negeri 3 Krapyak Jepara. This research using experiment method type quantitative research with research design Pretest Posttest Control Group Design. The population in this research is graders IV SD Negeri 3 Krapyak Jepara which amount 48 students. Retrieval sample used Probability Sampling Technique type Simple Random Sampling. By virtue of one sample t test, providable tcount > ttable (10,371 > 1,714) so Ha accepted, its mean problem solving ability of the student that given Numbered Heads Together model over 65, from calculation of the test to test with two sample t test, providable tcount = 9,052. Because ?óÔé¼ÔÇ£ 2,01< 9,052 > 2,01 so Ha accepted, its mean problem solving ability of the student that given Numbered Heads Together model better than student who was given the conventional model and the result of double correlation test calculation result Ryx1x2 = 0,946 then testing its significance using F test with the result Fcount> Ftable(89,5 > 3,47) so the coefficient of double correlation that found is significant. Its mean there is a strong correlation between cooperation and braveness toward problem solving ability. Thus, it can be concluded that the Numbered Heads Together model having an affect on problem solving ability of?é?á the student in thematic integrative class IV SD Negeri 3 Krapyak Jepara.